Speed control in DC and AC drives - Reinel Beltran Aguedo; Ania Lussón Cervantes; José Ricardo Núñez Alvarez; Yolanda Llosas Albuerne (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Three speed-control strategies for DC and AC drives are presented in this study: a proportional integral derivative (PID) control strategy; an internal model control (IMC); and a state-space control by pole assignment with full state observer (ESSO). The three strategies are applied to a case study, demonstrating the potential of each one. Experimental identification was used to obtain the drive models used for the synthesis of the controllers. The three strategies showed satisfactory results when compared with the requirements imposed on the system, in addition to the good rejection of disturbances. However, the IMC strategy showed itself to be a little softer and with no maximum overshoot, which in some cases and some applications is usually a restriction.